STUDYING THE IMPORTANCE OF OATS AND CARVINE SEEDS IN FOLK MEDICINE (Eureka Journal of Physical and Chemical Research, 2025)
The article analyzes information on the chemical composition, medicinal properties , and scientific medical applications of oat (Avena sativa L.) and coriander seeds ( Coriandrum sativum L ) . These plants have medicinal properties and are used to treat many diseases, including cardiovascular, neurological, gastrointestinal, respiratory, metabolic, renal, and hepatic diseases. This review provides an understanding of the role of these plants in medicine in the treatment of various diseases.
Keywords: Avena sativa L., Coriandrum sativum L, diabetes, obesity, antioxidant, hepatoprotective, anti - inflammatory, cardiovascular diseases.